ANALISIS SEBARAN DAN KEBUTUHAN GURU GEOGRAFI PADA SMA NEGERI DI OKU TIMUR - Dewi Rosita; I Gede Sugiyanta; Sudarmi Sudarmi (JPG (Jurnal Penelitian Geografi), 2014)
The purpose of this study was to obtain information on the distribution geography teacher of Senior High School, the number of teachers required geography , and educational background geography teacher at Senior high school in Ogan Komering Ulu Timur South Sumatra Province in 2013 . The method used is descriptive method. The population in this study were 38 teachers of geography . The data collecting techniques that were used interview, and documentation. Analysis using calculate requirement of teachers. The results indicate: (1) The total requirement of Senior High School geography teacher at Ogan Komering Ulu Timur South Sumatra Province in 2013 was 23 teachers. (2) 63% of teacher were graduate of S1 Geography Education and 37% of teacher were graduate of S1 Non Geography Education , (3) Distribution of geography teachers in Senior high school in Ogan Komering Ulu Timur South Sumatra Province in 2013 is random.Tujuan penelitian ini adalah untuk mendapatkan informasi mengenai sebaran guru geografi SMA Negeri, jumlah guru geografi yang dibutuhkan, dan latar belakang pendidikan guru geografi pada SMA Negeri di Kabupaten Ogan Komering Ulu Timur Provinsi Sumatera Selatan Tahun 2013. Metode yang digunakan adalah metode deskriptif. Populasi dalam penelitian ini adalah 38 guru geografi. Alat pengumpulan data yaitu wawancara terstruktur dan dokumentasi. Teknik analisis data menggunakan teknik perhitungan kebutuhan guru. Hasil penelitian menunjukkan: (1) Total kebutuhan guru geografi pada SMA Negeri di Kabupaten Ogan Komering Ulu Timur Provinsi Sumatera Selatan Tahun 2013 adalah 23 guru. (2) 63% guru geografi yang lulusan S1 Pendidikan Geografi dan 37% guru geografi yang lulusan Non S1 Pendidikan Geografi, (3) Sebaran guru geografi pada SMA Negeri di Kabupaten Ogan Komering Ulu Timur Provinsi Sumatera Selatan Tahun 2013 adalah acak.Kata kunci: kebutuhan guru geografi, ogan komering ulu timur , sebaran guru.